Analysis of total coliform and escherichia coli (e. coli) in freshwater and marine bivalves. - Norli, Mohamad Syahmi Iskandar (Pusat Pengajian Kesihatan, 2015)
Bivalve molluscs commonly associated with many foodborne disease outbreaks. Total coliform and E. coli are always being used as microbial indicator to determine fecal pollution level in bivalves and water quality status. The objective of this study is to analyze the presence of total coliform and Escherichia coli in selected freshwater bivalves and marine bivalves. In this study, two freshwater bivalves: blood cockle (Anadara granosa) and Asian clam (Corbicula fluminea) were selected while two marine bivalves involved in this study were oysters (Crassostrea spp.) and carpet clam (Paphia textile}. Microbiological analyses conducted through were conventional rapid test method by using 3M Petri film E. co/z'/Coliform Count Plate. All samples were analyzed in term of raw or fresh sample and cooked with different time interval. Results of these analyses showed that all raw samples were contaminated with total coliform and E. coli. Total coliform and E. coli were also found in lightly cooked bivalves (5 and 10 minutes cooking time) and not in fully cooked bivalves (15 and 20 minutes cooking time) except for Anadara granosa and Paphia textile. Corbicula fluminea identified as most contaminated bivalves as compared to other samples. In conclusion, raw and lightly cooked bivalves are highly contaminated with pathogenic bacteria and unsafe for human consumption. In order to reduce and eliminate number of bacteria, bivalves must be cooked thoroughly with proper cooking temperature and method.